PENGARUH PENERAPAN METODE PEMBELAJARAN CROSSWORD PUZZLE BERBASIS APLIKASI PUZZLE MAKER TERHADAP HASIL BELAJAR MAHASISWA - Sri Maya; Nurhidayah Nurhidayah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to determine the effect of the Crossword Puzzle application based on the Puzzle Maker application method on learning outcomes of biology education students at the Muslim University of Maros on the concept of Kingdom Animalia. This research was a quantitative type of research using the Quasi Experiment method. The research comparing two classes, the experimental class with the Crossword Puzzle method treatment, and the control class with conventional learning. The results showed that the post-test score of the experiment class was 78.15 with the completeness category of 83.3 %. Compared to the control class, the average score of learning outcomes was 64.07 with the completeness category of 8.3%. The hypothesis testing, the P-value for the pretest-posttest of the experiment class was 0.001 (????<0.05). It indicates that the Crossword Puzzle learning method based on the Puzzle Maker application increased in learning outcomes of biology education students at the Muslim University of Maros on the Kingdom Animalia concept.